2009
DOI: 10.1002/jts.20390
|View full text |Cite
|
Sign up to set email alerts
|

The psychological health of contractors working in war zones

Abstract: This study examines the psychological health of contractors working in war zones. Seventy-nine contractors completed an Internet-based psychiatric assessment. The sample was exclusively male with a mean age of 43 (SD = 7) years. The number of contractors whose scores exceeded the cutoff points for depression, psychological distress, and excessive weekly alcohol consumption were 15 (20%), 21 (28%), and 13 (17%), respectively. A third of contractors had posttraumatic stress disorder (PTSD) scores in the moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 12 publications
1
10
1
Order By: Relevance
“…An estimated 126 000 security contractor staff have been deployed in Iraq since the beginning of combat operations in 2003, with a large number of national defence staff (civil-servants), journalists and other news media staff also working in operational theatres 4 7 8 27. The majority of non-military personnel working in theatre appear to be security contractors who themselves are most often former members of the Armed Forces 6. There may then be, some similarities between this subpopulation of personnel deployed alongside the Armed Forces and the deployed Armed Forces personnel themselves.…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 126 000 security contractor staff have been deployed in Iraq since the beginning of combat operations in 2003, with a large number of national defence staff (civil-servants), journalists and other news media staff also working in operational theatres 4 7 8 27. The majority of non-military personnel working in theatre appear to be security contractors who themselves are most often former members of the Armed Forces 6. There may then be, some similarities between this subpopulation of personnel deployed alongside the Armed Forces and the deployed Armed Forces personnel themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers also face the challenge of bringing attention to families who might otherwise suffer invisibly. Displaced and disenfranchised families in Africa, women and girls in societies where low status exacerbates their vulnerability, and private contractors who face elevated rates of death and injury in Iraq (Feinstein & Botes, 2009) all deserve to have their experiences understood. Beyond simply documenting the content and prevalence of concerns, researchers also must push forward to develop theory‐driven models that will help to explain variations among individuals and families, ultimately generating insights that will help to prevent mass violence, prepare families for it, and intervene in its aftermath.…”
Section: Concluding Thoughtsmentioning
confidence: 99%
“…When civilian contractors suffer physical injuries during employment in a combat zone, a possibility of mental health struggles also exists. After completing the Trauma History Questionnaire, a group of civilian contractors were found to exceed cutoff scores for depression, psychological distress, and alcohol consumption (Feinstein & Botes, 2009). Similarly, Brenner, et al (2008) found that veterans diagnosed with PTSD were experiencing a reduced amount of emotional responses post-deployment and an increased sense of disconnection with others.…”
Section: Chapter 2 Literature Reviewmentioning
confidence: 98%